Tourism Potential Development Strategy Using the Military Model To Improve Local Economic Development in Indonesia - Mutiara Annissa Oktapiani; Lukman Yudho Prakoso; Suwito Suwito (International Journal Of Humanities Education and Social Sciences (IJHESS), 2024)
Indonesia has an incredible diversity of natural resources and is one of the largest countries in the Asian region and even in the world. These natural resources can boost the local economy through tourism and various businesses. Therefore, to increase regional economic growth through the development of tourism potential, it is necessary to make careful plans and strategies. The purpose of this study is to determine methods that can be used to increase regional economic growth through the development of tourism potential. This study used a qualitative description approach. The goal is to provide an accurate picture of a particular characteristic, situation, symptom, or group of individuals, or to identify the frequency or distribution of symptoms. In military science, the strategic concept of "ends, ways, and means" developed by Arthur F. Lykke Jr. can be used to increase tourism potential. This concept explains that the existence of the tourism sector must include three objectives of this strategy: 1) Ends, which is a strategic concept centered on the ultimate goal of a tourism management strategy; 2) Means, which are methods or approaches used to achieve goals; and 3) Means, which is By implementing this idea, it is hoped that regional tourism growth can generate prosperity and economic independence, as well as a significant contribution to regional and national income.